Living in Urban Areas, Low Education, Cognitive Function, and Medication Adherence Are Factors Related to Major Depression among Epilepsy Patients in Manado, Indonesia (Indian Journal of Public Health Research & Development, 2020)
Purpose: The aim of this study was to identify factors related to major depression among epilepsy patientsin city of Manado.Methods: This was a cross-sectional study conducted in Neurology Clinic and appropriate bivariate analysiswas used to test the relationship between sociodemographic and clinical variables with major depression.Findings: Living in urban areas, low education, low cognitive function, and low medication adherence arefactors related to major depression. The relationship between medication adherence and depression is foundin previous studies but the other significant factors in this study are not.Conclusion: Our region has some particular factors related to major depression among epilepsy patients.These findings considered in designing local treatment strategy and health policy
Keywords: Epilepsy, major depression, Manado-Indonesia, related factors.